EXPLORING MOUNT EVEREST - Rathburn, Betsy; Downs, Kieran; Brink, Josh (Minneapolis, MN : Bellwether Media, 2023)
Mount Everest is the highest point on Earth! In this title, engaging text introduces the dangers of scaling Everest as well as how explorers prepare for the journey. Special features highlight the peak's place in the world, profile a famous explorer, and explore a danger posed by the journey. Readers' skills will climb as they journey through this thrilling book about climbing to the top of the world!
Includes index
Bibliography : page 23
Ages 7-12 Grades 4-6
Keywords: Outdoor life -- Juvenile literature; Outdoor recreation -- Juvenile literature; Extreme sports -- Recreations -- Juvenile literature; Everest, Mount (China and Nepal) -- Juvenile literature